Mast cell degranulation and calcium influx are inhibited by an Echinacea purpurea extract and the alkylamide dodeca-2E, 4E-dienoic acid isobutylamide. (15th February 2018) - Gulledge, Travis V.; Collette, Nicholas M.; Mackey, Emily; Johnstone, Stephanie E.; Moazami, Yasamin; Todd, Daniel A.; Moeser, Adam J.; Pierce, Joshua G.; Cech, Nadja B.; Laster, Scott M.
Abstract: Ethnopharmacological relevance: Native Americans used plants from the genus Echinacea to treat a variety of different inflammatory conditions including swollen gums, sore throats, skin inflammation, and gastrointestinal disorders. Today, various Echinacea spp . preparations are used primarily to treat upper respiratory infections. Aim of the study: The goal of this study was to evaluate the effects of an ethanolic E. purpurea (L) Moench root extract and the alkylamide dodeca-2E, 4E-dienoic acid isobutylamide (A15) on mast cells, which are important mediators of allergic and inflammatory responses. Inhibition of mast cell activation may help explain the traditional use of Echinacea . Materials and methods: A15 was evaluated for its effects on degranulation, calcium influx, cytokine and lipid mediator production using bone marrow derived mast cells (BMMCs) and the transformed rat basophilic leukemia mast cell line RBL-2H3. Methods included enzymatic assays, fluorimetry, ELISAs, and microscopy. A root extract of E. purpurea, and low and high alkylamide-containing fractions prepared from this extract, were also tested for effects on mast cell function. Finally, we tested A15 for effects on calcium responses in RAW 264.7 macrophage and Jurkat T cell lines. Results: A15 inhibited ß-hexosaminidase release from BMMCs and RBL-2H3 cells after treatment with the calcium ionophore A23187 by 83.5% and 48.4% at 100 µM, respectively. Inhibition also occurred following stimulation with IgE anti-DNP/DNP-HSA. In addition, A15 inhibited 47% of histamine release from A23187-treated RBL-2H3 cells. A15 prevented the rapid rise in intracellular calcium following FcεRI crosslinking and A23187 treatment suggesting it acts on the signals controlling granule release. An E. purpurea root extract and a fraction with high alkylamide content derived from this extract also displayed these activities while fractions with little to no detectable amounts of alkylamide did not. A15 mediated inhibition of calcium influx was not limited to mast cells as A23187-stimulated calcium influx was blocked in both RAW 264.7 and Jurkat cell lines with 60.2% and 43.6% inhibition at 1 min post-stimulation, respectively. A15 also inhibited the release of TNF-α, and PGE2 to a lesser degree, following A23187 stimulation indicating its broad activity on mast cell mediator production. Conclusions: These findings suggest that Echinacea extracts and alkylamides may be useful for treating allergic and inflammatory responses mediated by mast cells. More broadly, since calcium is a critical second messenger, the inhibitory effects of alkylamides on calcium uptake would be predicted to dampen a variety of pathological responses, suggesting new uses for this plant and its constituents. Graphical abstract: